Upaya Peningkatan Pengetahuan melalui Promosi Kesehatan Penyakit Keganasan pada Anak di SMAN Titian Teras Jambi - Suryati Suryati; Suryadi Imran; Devi Yusmahendra; Apriani Apriani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Malignant disease, or more commonly known as cancer, is a disease characterized by the growth and spread of abnormal cells in the body. Malignant disease in children, although rare, is the second leading cause of death in children in developed countries after accidents. Data from the Union for International Cancer Control (UICC), there are about 176,000 children worldwide who are diagnosed with cancer each year. In Indonesia, there are about 11,000 cases of childhood cancer every year. Recognizing the signs of malignancy at an early age can increase the cure rate and life expectancy of children who experience it. Therefore, it is necessary to provide knowledge to children about early detection and prevention of cancer in children. This activity is carried out by the method of providing health promotion in the form of counseling at SMAN Tititan Teras Jambi. This activity is carried out by the method of counseling. The activity has been carried out in October 2021. The output of this activity is an increase in student knowledge. The results of the activity evaluation, it was found that there were differences in the level of knowledge of students who were given counseling with students who were not given counseling (scores of 7.03 and 5.63, respectively). Increasing knowledge is expected to improve student attitude and behavior to recognize early signs & symptoms of malignancy, so that diagnosisand management can be carried out quickly & precisely